2007
DOI: 10.1161/circulationaha.106.659730
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic and Functional Consequences of Bone Marrow–Derived Multipotent Progenitor Cell Transplantation in Hearts With Postinfarction Left Ventricular Remodeling

Abstract: Background-The present study examined whether transplantation of adherent bone marrow-derived stem cells, termed pMultistem, induces neovascularization and cardiomyocyte regeneration that stabilizes bioenergetic and contractile function in the infarct zone and border zone (BZ) after coronary artery occlusion. Methods and Results-Permanent left anterior descending artery occlusion in swine caused left ventricular remodeling with a decrease of ejection fraction from 55Ϯ5.6% to 30Ϯ5.4% (magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
197
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(212 citation statements)
references
References 34 publications
9
197
1
4
Order By: Relevance
“…Similarly, ischemic limb studies have also detected enhanced angiogenic factor expression at the site of injury following MSC injection [38]. The increase in capillary density one month after MSC injection into infarcted hearts has also been shown [37,40,42]. The fact that these improvements persist while only a negligible amount of MSC remains in the myocardium, can also be used to support neovascularization as a main beneficiary mechanism.…”
Section: Mesenchymal Stem Cells (Msc)mentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, ischemic limb studies have also detected enhanced angiogenic factor expression at the site of injury following MSC injection [38]. The increase in capillary density one month after MSC injection into infarcted hearts has also been shown [37,40,42]. The fact that these improvements persist while only a negligible amount of MSC remains in the myocardium, can also be used to support neovascularization as a main beneficiary mechanism.…”
Section: Mesenchymal Stem Cells (Msc)mentioning
confidence: 91%
“…Second, many argue that it is an increase in tissue revascularization [36][37][38][39]. Clusters of MSC have been shown to express key vessel markers, such as von Wille-brand factor, while cardiac markers were absent [36].…”
Section: Mesenchymal Stem Cells (Msc)mentioning
confidence: 99%
“…12 Briefly, animals were anesthetized with 2% inhaled isoflurane and positioned in a supine position within the scanner.…”
Section: Heart Function Assessmentmentioning
confidence: 99%
“…Myocardial injury and stunning therefore usually originate in the endocardium and, with time, progress to include the epicardium. 26 In general, VEGF expression is activated under hypoxic conditions, a reasonable mechanism for holding oxygen tension constant. 27 Some previous investigators suggested that a soluble VEGF receptor (ie, sVEGFR1) increases in response to hypoxia.…”
Section: Myocardial Layer-specific Recoverymentioning
confidence: 99%